Biogeography and species delimitation of the rheophilic suckermouth catfish genus Pseudolithoxus (Siluriformes: Loricariidae), with the description of a new species from the Brazilian Amazon. Issue 6 (18th August 2018) - Collins, Rupert A.; Bifi, Alessandro G.; de Oliveira, Renildo R.; Ribeiro, Emanuell D.; Lujan, Nathan K.; Rapp Py-Daniel, Lúcia H.; Hrbek, Tomas
Abstract : The rapids-dwelling suckermouth catfish genus Pseudolithoxus was previously only known from the Guiana-Shield-draining Orinoco and Casiquiare river systems of Colombia and Venezuela, but new records have expanded this range considerably further into the Amazon basin of Brazil, and include occurrences from rivers draining the northern Brazilian Shield. These highly disjunct records are now placed in an evolutionary and phylogeographic context using a dated species tree constructed from mitochondrial ( Cytb ) and nuclear ( RAG1 ) gene sequence data. Due to mito-nuclear discordance, we also delimit the putative species using statistical coalescent models and a range of additional metrics. We infer that at least two species of Pseudolithoxus are present in the Amazon basin: P . nicoi, previously only recorded from the río Casiquiare, but now also reported from the upper rio Negro, and a new species, which we describe herein from south-draining Guiana Shield and north-draining Brazilian Shield. Our data reject a simple model of Miocene vicariance in the group following uplift of the Uaupés Arch separating the Orinoco and Amazon systems, and instead suggest more complex dispersal scenarios through palaeo-connections in the Pliocene and also via the contemporary rio Negro and rio Madeira in the late Pleistocene. www.zoobank.org/urn:lsid:zoobank.org:pub:46A6BEC1-1A1B-4244-80-A6-FD9CF8DA0384 .